Legal Certainty and Protection for Original Certificate Holders in Disputes Regarding the Issuance of Replacement Certificates - Dewani Kireina Tjitrasmoro; Benny Djaja (IHSA Institute, 2026)
This study aims to examine the legal protections afforded to buyers under a Sales and Purchase Agreement (SPA) and the legal certainty afforded to holders of original certificates in cases of replacement certificate issuance. This research employed a qualitative method with a normative-empirical approach through a review of laws and regulations, analysis of land documents, and a review of relevant cases. The results indicate that SPA does not provide sufficient legal protection if the land does not meet administrative and material requirements, particularly when the certificate used as the basis for the transaction is proven to be administratively flawed or is in dispute. The issuance of replacement certificates, the application of the principles of legality, accuracy, and prudence, are crucial in preventing and mitigating these risks. This study emphasizes the need to strengthen verification mechanisms and administrative oversight to ensure legal protection and to avoid land disputes